Blender 3D : characters, machines, and scenes for artists : gain the insights and techniques you need to give life to your own custom characters, machines, and scenes in Blender 3D /: characters, machines, and scenes for artists : gain the insights and techniques you need to give life to your own custom characters, machines, and scenes in Blender 3D. (2016) - Valenza, Enrico
No abstract available